2018
DOI: 10.1097/md.0000000000010386
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin 37 (rs3811047) polymorphism and multiple autoimmune diseases in a Chinese population

Abstract: Objective:Emerging evidence suggests that interleukin 37 (IL-37) plays an important role in the pathogenesis of several autoimmune diseases (ADs), but the correlations are still unclear. We conducted a meta-analysis to explore whether IL-37 gene (rs3811047) polymorphism was associated with susceptibility to multiple ADs in a Chinese population.Methods:Relevant studies were searched in the PubMed, Embase, Chinese National Knowledge Infrastructure, and Chinese Wangfang databases up to August 31, 2017. Odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study is the first to discuss the relationship between this locus and susceptibility to chronic HBV infection in the Chinese Han population, and we also did not obtain statistically significant results. However, evidence suggests that rs3811047 is associated with susceptibility to PU, ankylosing spondylitis, RA, autoimmune thyroid diseases and Behcet's disease (Davarpanah et al., 2020; Lin et al., 2018; Özgüçlü et al., 2019; Tan et al., 2016). Interestingly, a similar study found a significant association between the two SNPs and susceptibility to COVID‐19 among Iraqi patients (Ahmed & Ad'hiah, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to discuss the relationship between this locus and susceptibility to chronic HBV infection in the Chinese Han population, and we also did not obtain statistically significant results. However, evidence suggests that rs3811047 is associated with susceptibility to PU, ankylosing spondylitis, RA, autoimmune thyroid diseases and Behcet's disease (Davarpanah et al., 2020; Lin et al., 2018; Özgüçlü et al., 2019; Tan et al., 2016). Interestingly, a similar study found a significant association between the two SNPs and susceptibility to COVID‐19 among Iraqi patients (Ahmed & Ad'hiah, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Variant rs3811047 has been associated with susceptibility to or protection against several infectious, inflammatory, and autoimmune diseases as ankylosing spondylitis, rheumatoid arthritis, auto-immune thyroid disease, Behcet’s disease, and Vogt-Koyanagi-Harada disease [ 28 ]. The current study showed that TG genotype of rs3811046 may increase the risk of developing COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted this variant more than rs3811046. This SNP has been associated with susceptibility to or protection against several infectious, inflammatory and autoimmune diseases (Al-Anazi et al, 2019;Allam et al, 2016;Lin et al, 2018;Offenbacher et al, 2018;Özgüçlü et al, 2019). Tuberculosis is the only infectious disease of the respiratory tract studied and susceptibility to disease was not associated with rs3811047, but C allele and CC genotype of another IL37 gene SNP (rs2723176) occurred significantly more frequently in patients with active tuberculosis (Allam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to inflammatory and autoimmune diseases, G allele and GG genotype of rs3811047 SNP showed significantly increased frequencies in Chinese patients with Behcet's disease in comparison with controls (Tan et al, 2016), but these findings were not confirmed in Turkish patients, and Behcet's disease did not show association with rs3811047 ( Özgüçlü et al, 2019). A meta-analysis of multiple autoimmune diseases in Chinese patients (ankylosing spondylitis, rheumatoid arthritis, autoimmune thyroid disease, Behcet's disease and Vogt-Koyanagi-Harada disease) revealed a significant association between rs3811047 variant and susceptibility to autoimmune diseases in four genetic models (allele, recessive, dominant and heterozygous) (Lin et al, 2018). In ankylosing spondylitis patients, it was interesting to note that expressions of Creactive protein and erythrocyte sedimentation rate (inflammatory markers) were influenced by GG genotype of rs3811047 (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation